TINDAK TUTUR DIREKTIF DALAM NOVEL LELAKI YANG MENGGENGGAM AYAT-AYAT TUHAN KARYA TAUFIQURRAHMAN AL-AZIZY - Susilawati, Karmi; Chan, Wirsal; Marni, Silvia (Pendidikan Bahasa Indonesia, 2014)
The central issue of this research is directive speech acts in a novel Lelaki yang menggenggam Ayat-ayat Tuhan  by  Taufiqurrahman Al-Azizy. This study aimed to describe the directive speech acts in the novel  Lelaki yang menggenggam Ayat-ayat Tuhan by  Taufiqurrahman Al-Azizy.  This research is a qualitative research method is descriptive content analysis. These results indicate a directive speech acts can be seen from the figures of speech in the novel  Lelaki  yang menggenggam  Ayat-ayat Tuhan  by  Taufiqurrahman Al-Azizy. Type of directive speech acts contained in the novel include speech acts ordered,  pleaded speech acts,  speech acts advising, challenging speech acts and speech act suggests.  Through a directive speech act character in the novel  Lelaki yang menggenggam Ayat-ayat Tuhan  by  Taufiqurrahman Al-Azizy we could take a lesson about the purpose of our life in Gods power. Because this novel is a novel reflection soul.